Penerapan Preventive Maintenance dan Pemasangan Emergency Lamp Dalam Minimasi Product Defect Akibat Heater Terhadap Produk Kemasan - Maulana, Helmi; Khoiroh, Siti Muhimatul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Plant printing is a company unit tasked with fulfilling product packaging needs. In the production of printing plants from July to December, it was found that an average of 4% of products had defects (defects) exceeding the allowable tolerance limit of 2% per month, the biggest cause of problems with one of the machine components, namely the heater component. In these components found downtime of 3900 minutes for 3 months. Based on these problems, it is necessary to take preventive measures with a preventive maintenance approach by determining the schedule which is obtained from the calculation of the mean time to failure (MTTF) that the recommended maintenance interval is once every 5 days. Plus another improvement with the installation of an emergency lamp if the heater is indicated to be experiencing a mismatch. After the two approaches and improvements were carried out, a decrease in the number of product defects was obtained where the defect in the previous 6 months averaged 4% and in the following month after implementation the number of defects decreased to only 1.83%.